A simple procedure for the preparation of laponite and thermoplastic starch nanocomposites: Structural, mechanical, and thermal characterizations. (February 2013) - Aouada, Fauze A; Mattoso, Luiz HC; Longo, Elson
The aim of this article is to propose advances for the preparation of hybrid nanocomposites prepared by the combination of intercalation from solution and melt-processing methods. This research investigates the effect of the laponite RDS content on the thermal, structural, and mechanical properties of thermoplastic starch (TPS). X-ray diffraction was performed to investigate the dispersion of the laponite RDS layers into the TPS matrix. The results show good nanodispersion, intercalation, and exfoliation of the clay platelets, indicating that these composites are true nanocomposites. The presence of laponite RDS also improves the thermal stability and mechanical properties of the TPSmatrix due to its reinforcement effect which was optimized by the high degree of exfoliation of the clay. Thus, these results indicate that the exfoliated TPS–laponite nanocomposites have great potential for industrial applications and, more specifically, in the packaging field.